Normalization of timed neuropsychological tests with the PATA rate and nine‐hole pegboard tests. Issue 3 (6th May 2017) - Saccà, Francesco; Costabile, Teresa; Abate, Filomena; Liguori, Agnese; Paciello, Francesca; Pane, Chiara; De Rosa, Anna; Manganelli, Fiore; De Michele, Giuseppe; Filla, Alessandro
Abstract : Introduction: Despite neurological patients show frequent physical impairment, timed neuropsychological tests do not take this into account during scoring procedures. Objective: We propose a normalization method based on the PATA Rate Task (PRT) and on the nine‐hole pegboard test (9HPT) as a measure of dysarthria and upper limb dysfunction. Methods: We tested 65 healthy controls on timed neuropsychological tests (Attentional Matrices [AM], Trail Making Test, Symbol Digit Modalities Test, Verbal Fluencies) to determine the time spent on phonation or on hand movement during test execution. We developed correction formulas to normalize test times considering the patient's PRT/9HPT, their normality limits, and the test timing. We tested the method on 24 patients with Friedreich Ataxia (FRDA), as a model of motor and speech impairment. Results: In healthy controls, phonation or hand movement is 13.5–61.7% of total test time. In FRDA patients, the effect of normalization improved all test results (range: 0.51–48.4%; p  < .001). FRDA patients had worst scores in all tests when compared to controls, and the difference remained significant after correction except for the AM. At the individual level, the normalization method improved equivalent scores with fever patients showing impaired scores after correction. Conclusions: We propose an innovative normalization method to reduce the impact of neurological disability on timed neuropsychological tests. This could be easily integrated in a clinical setting, as it requires a simple preliminary test with the PRT and 9HPT.